Cartographies génériques, spatiales et identitaires en Afrique du Sud : Margie Orford, Lauren Beukes, Henrietta Rose-Innes - Joseph-Vilain, Mélanie (Études littéraires africaines, 2014)
This article examines how three South African novelists, Margie Orford, Lauren Beukes and Henrietta Rose-Innes, use crime fiction to write their country. After a brief survey of the rapid development of crime fiction in South Africa and of the critical response it received, the article proposes a reading of Like Clockwork, Zoo City and Nineveh, whereby their respective contribution to crime fiction displays three major features : first, Orford’s novel chimes in with generic conventions ; second, Beukes’s novel combines features borrowed from both crime fiction and science fiction ; and last, Rose-Innes’s novel displaces the detective story narrative into a context where « murder » is invested with a symbolic meaning. By handling the investigation theme in a variety of ways, the three novelists adapt it to the South African context and besides show that the feminine body fits in more or less problematically within the space of the city and of the nation.